LIVING ALONGSIDE NATURE’S FURY: UNDERSTANDING VOLCANIC ERUPTIONS AND FLASH FLOODS - Habibullayeva Ayisha Hamidulla qizi; Mannobov Abdumalik Mansurjon oʻgʻli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, explores two of the most awe-inspiring yet destructive natural hazards on Earth — volcanic eruptions and flash floods. The author investigates the scientific causes behind each phenomenon, describes the scale of damage they can inflict on human lives and the environment, and outlines the essential precautions every person should know. The article encourages young readers to view disaster preparedness not as a burden, but as a vital life skill.